Waterfront Regeneration: A Tool to Reverse the Declining Riverfront in Limbang, Sarawak - Toh, Sunny Tian Kiong; Kozlowski, Marek (MAJ - Malaysia Architectural Journal, 2020)
As a result of modernisation and globalisation, there is growing concern to regenerate decayed parts of the cities. Urban regeneration often takes place in areas such as existing waterfront development, historic preservation sites, reutilising abandoned or decayed buildings and also on-site that is situated at central residential or commercial areas with high human activity. In Malaysia, urban regeneration at the waterfront and coastal towns are still in the early stage of development although numerous attempts have been made by the local council and state governments to revitalise riverfront towns in Malaysia. This paper aims at exploring the concept of waterfront regeneration and its strategies as tools for the regeneration of small riverfront cities and towns in Malaysia. To further carry out this research Limbang, Sarawak has been selected as the case study area. The research methodology is based on the identification of problem supported by research questions and objectives. The major findings of this research paper indicate that urban regeneration at waterfront area can enhance the socio-economic and cultural environments when based on integrated urban planning. The introduction of waterfront regeneration development will involve stakeholders and benefit the local community while creating a unique sense of place and image for the declining town. The findings of this study reveal that improving the sense of place and introducing placemaking techniques benefits the community and play an important role in urban regeneration.